Avaliação do contexto no atendimento das equipes de consultório na rua às pessoas com tuberculose no estado do Rio Grande do Norte - Nascimento, Camila Priscila Abdias do (2024)
The homeless population is 56 times more susceptible to tuberculosis and is 50% less likely to complete treatment successfully, in addition to presenting abandonment and mortality rates that are 2.9 and 2.5 times higher, respectively. Given this scenario, the Ministry of Health implemented Street Clinics to expand access to health services for this population. In this sense, the objective was to evaluate the influence of the context of the teams in the care of people with tuberculosis in the State of Rio Grande do Norte. An evaluative study of the normative type and evaluative research was carried out, with a qualitative and quantitative approach, emphasizing the degree of implementation, structure/process/result and influence of the context, of the street clinic team. The study was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte, under opinion number 6,046,884. The study population consisted of 22 professionals who work directly or indirectly in the street clinic team. With regard to evaluative research, value judgment was used to analyze the relationships between the intervention and the context. The qualitative data obtained were analyzed using the content analysis technique proposed by Bardin (2011). As results and discussions, in terms of degree of implementation, the Structure dimension was classified as partially implemented. The Process dimension, in turn, was classified as fully implemented, but with some divergences from reality, according to what was revealed by the statements of the professionals interviewed when exposing their perceptions. As results and discussions, in terms of degree of implementation, the Structure dimension was classified as partially implemented. The Process dimension, in turn, was classified as fully implemented, but with some divergences from reality, according to what was revealed by the statements of the health professionals and managers interviewed when exposing their perceptions. In relation to the perceptions mentioned by eCnaR professionals, four thematic categories were raised: (I) social determinants of health and homelessness based on Milton Santos; (II) territory as a socially produced space and the responsibilities and activities of eCnaR and health managers; (III): power relations and the influence of context on eCnaR actions; and (IV) appropriation of the territory – potentialities and challenges in daily work. Considering the divergences between practical implementation and professionals' perception, we can infer that, even in a context of partial implementation, professional practice reflects an intuitive understanding and aligned with the principles of Milton Santos' theory.